Determination of Suspects Based on Regulation of the Chief of the Indonesian National Police Number 6 of 2019 Concerning Criminal Investigation (Case Study Number: 10/Pid.Pra/2024/PN Bdg) - Robiatul Adawiyah; Nynda Fatmawati O (Dinasti Research, 2025)
This research aims to find out whether the arrangements for determining suspects in National Police Chief Regulation Number 6 of 2019 concerning Criminal Investigations are in accordance with the provisions in the Criminal Procedure Code (KUHAP). This research uses normative research methods with a prescriptive approach. The data used in this research is secondary data obtained from library materials, such as books, journals and statutory regulations. The results of the research show that